COVID-19 in Immunocompromised Hosts: What We Know So Far - Fung, Monica (Clin Infect Dis, 2020)
The coronavirus disease 2019 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused significant morbidity and mortality for patients and stressed healthcare systems worldwide. The clinical features and outcomes of COVID-19 among immunosuppressed patients, who are at presumed risk of more severe disease but who may also have decreased detrimental inflammatory responses, are not well characterized. We review the existing literature on COVID-19 among immunocompromised populations ranging from patients with cancer and solid-organ transplant recipients to patients with HIV and those receiving immunomodulatory therapy for autoimmune disease. Patients with malignancy and solid-organ transplant recipients may be at increased risk of severe COVID-19 disease and death, whereas for those with other types of immunocompromise, current evidence is less clear. Overall, further prospective controlled studies are needed to determine the attributable risk of immunocompromising conditions and therapies on COVID-19 disease prognosis.